Immediate delivery or expectant management in gestational diabetes at term: the GINEXMAL randomised controlled trial. - Alberico, S; Erenbourg, A; Hod, M; Yogev, Y; Hadar, E; Neri, F; Ronfani, L; Maso, G (BJOG, 2017)
OBJECTIVE: To evaluate maternal and perinatal outcomes after induction of labour versus expectant management in pregnant women with gestational diabetes at term. DESIGN: Multicentre open-label randomised controlled trial. SETTING: Eight teaching hospitals in Italy, Slovenia, and Israel. SAMPLE: Singleton pregnancy, diagnosed with gestational diabetes by the International Association of Diabetes and Pregnancy Study Groups criteria (IADPSGC), between 38 and 39 weeks of gestation, without other maternal or fetal conditions. METHODS: Patients were randomly assigned to induction of labour or expectant management and intensive follow-up. Data were analysed by 'intention to treat'. MAIN OUTCOME MEASURES: The primary outcome was incidence of caesarean section. Secondary outcomes were maternal and perinatal mortality and morbidity. RESULTS: A total of 425 women were randomised to the study groups. The incidence of caesarean section was 12.6% in the induction group versus 11.7% in the expectant group. No difference was found between the two groups (relative risk, RR 1.06; 95% confidence interval, 95% CI 0.64-1.77; P = 0.81). The incidence of non-spontaneous delivery, either by caesarean section or by operative vaginal delivery, was 21.0 and 22.3%, respectively (RR 0.94; 95% CI 0.66-1.36; P = 0.76). Neither maternal nor fetal deaths occurred. The few cases of shoulder dystocia were solved without any significant birth trauma. CONCLUSIONS: In women with gestational diabetes, without other maternal or fetal conditions, no difference was detected in birth outcomes regardless of the approach used (i.e. active versus expectant management). Although the study was underpowered, the magnitude of the between-group difference was very small and without clinical relevance. TWEETABLE ABSTRACT: Immediate delivery or expectant management in gestational diabetes at term?
Keywords: Adult; Delivery, Obstetric; Diabetes, Gestational; Female; Humans; Infant, Newborn; Israel; Italy; Maternal Mortality; Perinatal Mortality; Pregnancy; Pregnancy Outcome; Slovenia; Term Birth; Watchful Waiting

Does EMLA cream application interfere with the success of venipuncture or venous cannulation? A prospective multicenter observational study. - Schreiber, S; Ronfani, L; Chiaffoni, G P; Matarazzo, L; Minute, M; Panontin, E; Poropat, F; Germani, C; Barbi, E (Eur J Pediatr, 2013)
UNLABELLED: Venipuncture and intravenous cannulation are the most common painful procedures performed on children. The most widely used topical anesthetic is eutectic mixture of local anesthetics (EMLA). EMLA use is associated with a transient cutaneous vasoconstriction which can make it difficult to identify veins. We assessed with a prospective, multicenter, observational study whether EMLA interferes with venipuncture and intravenous cannulation. The primary study outcome was a success at first attempt in the course of venipuncture or venous cannulation. The study enrolled 388 children; 255 of them received EMLA and 133 did not. Eighty-six percent of procedures were successful at the first attempt in the EMLA group and 76.7 % in the no EMLA group. CONCLUSION: In this study, EMLA use did not interfere with the success of venipuncture or venous cannulation in children.
Keywords: Anesthetics, Local; Catheterization, Peripheral; Child; Child, Preschool; Female; Humans; Lidocaine; Logistic Models; Male; Ointments; Phlebotomy; Prilocaine; Prospective Studies; Vasoconstriction

Adverse effects during specific oral tolerance induction: in home phase. - Barbi, E; Longo, G; Berti, I; Matarazzo, L; Rubert, L; Saccari, A; Lenisa, I; Ronfani, L; Radillo, O; Ventura, A (Allergol Immunopathol (Madr), 2012)
BACKGROUND: Specific oral tolerance induction (SOTI) is a promising approach for severe food allergies. There are little data in the literature regarding the home-phase of SOTI, not only with regard to type and frequency of adverse reactions but also regarding the most suitable treatment and protocol. AIMS: To define the incidence and severity of adverse reactions, possible risk factors, and the safety and effectiveness of the home-phase of an original SOTI protocol in a large group of children with severe cow's milk (CM) allergy, after the hospital "rush" phase. METHODS: The study was conducted by recording in-home phase adverse events, success and failure as reported by parents, and calling families. Adverse reactions were treated following the International Guidelines, arbitrarily modified by introducing nebulised epinephrine for respiratory reactions, oral beclomethasone for acute gastric pain and oral cromolyn for recurrent gastric pain. RESULTS: Out of 140 patients, 132 were contacted; eight were inaccessible (follow-up 2-84 months). The number of adverse reactions was 1 in every 100 doses. The reactions were treated with nebulised epinephrine (221 reactions), IM epinephrine (6 reactions), and other drugs. Patients with high specific IgE levels (greater than 100 kU(A)/L) and lower CM dose (less than 5 ml) at the end of in-hospital phase showed a higher risk both for number of reactions and use of nebulised epinephrine. CONCLUSIONS: The home phase of SOTI was characterised by a significant number of adverse reactions, mostly managed with an acceptable rate of side effects. Nebulised epinephrine played a pivotal role in respiratory reactions.
Keywords: Adolescent; Adult; Age Factors; Allergens; Child; Child, Preschool; Desensitization, Immunologic; Epinephrine; Female; Food Hypersensitivity; Humans; Immune Tolerance; Immunoglobulin E; Male; Milk Hypersensitivity; Nebulizers and Vaporizers

Diagnosed child, treated child: food challenge as the first step toward tolerance induction in cow's milk protein allergy. - Longo, G; Berti, I; Barbi, E; Calligaris, L; Matarazzo, L; Radillo, O; Ronfani, L; Ventura, A (Eur Ann Allergy Clin Immunol, 2012)
BACKGROUND: Food challenge is required to assess tolerance in cow milk (CM) allergy. A positive challenge contraindicates the reintroduction of CM. Specific oral tolerance induction (SOTI) is a promising treatment. METHODS: All children admitted for a challenge were prospectively enrolled. To those tolerating between 2 and 150 ml a SOTI protocol was offered. Outcome, adverse reactions, parents' satisfaction were recorded. RESULTS: Out of 245 challenged patients, 175 reacted 122 out of 125, able to tolerate a minimum dose of 2 ml, underwent SOTI. After one year 75.4% were in an unrestricted diet, 16.1% tolerated between 5 and 150 ml, 8.5% stopped SOTI. Side effects were mild, parents' satisfaction was very high. CONCLUSIONS: The majority of children tolerating limited amounts of CM at the challenge acquires tolerance with SOTI without relevant side effects. Maintaining on an exclusion diet partially tolerant children should be considered debatable.
Keywords: Administration, Oral; Adolescent; Animals; Cattle; Child; Child, Preschool; Humans; Immune Tolerance; Infant; Milk Hypersensitivity; Milk Proteins; Self Administration

First trimester maternal serum PIGF, free β-hCG, PAPP-A, PP-13, uterine artery Doppler and maternal history for the prediction of preeclampsia. - Di Lorenzo, G; Ceccarello, M; Cecotti, V; Ronfani, L; Monasta, L; Vecchi Brumatti, L; Montico, M; D'Ottavio, G (Placenta, 2012)
OBJECTIVE: To evaluate the detection of pregnancy hypertensive disorders by integrating maternal history, serum biomarkers and uterine artery Doppler in the first trimester. METHODS: We prospectively recruited 2118 women that underwent an 11-13 weeks aneuploidy screening. We gathered information on maternal history, uterine artery Doppler and serum biomarkers (PAPP-A, PlGF, PP-13 and free β-hCG). Models were developed for the prediction of overall preeclampsia (PE), early-onset PE, late-onset PE and gestational hypertension (GH). For each outcome, we performed a multivariate logistic regression starting from the saturated model: adopting a step-down procedure we excluded all factors not statistically significant (p > 0.05). Sensitivity models only for statistically significant parameters were calculated from the ROC curves for fixed false-positive rates (FPR). RESULTS: Among 2118 women, 46 (2.17%) developed GH and 25 (1.18%) were diagnosed with PE, including 12 (0.57%) early-onset PE and 13 (0.61%) late-onset PE. For a fixed FPR of 10 and 5%, serum PlGF, free β-hCG and chronic hypertension identified respectively 67 and 75% of women who developed early-onset PE. In the model for the prediction of overall PE the combination of the uterine artery Doppler pulsatility index (UtA PI) with PlGF and chronic hypertension reached a sensitivity of 60% for a 20% of FPR. CONCLUSION: An integration of maternal characteristics and first trimester maternal serum biomarkers (free β-hCG and PlGF) provided a possible screening for early-onset PE. In the overall PE model, UtA PI turned out to be statistically significant but did not improve the detection rate.
Keywords: Adult; Biological Markers; Chorionic Gonadotropin, beta Subunit, Human; Cohort Studies; Female; Galectins; Humans; Hypertension, Pregnancy-Induced; Pre-Eclampsia; Pregnancy; Pregnancy Complications; Pregnancy Proteins; Pregnancy Trimester, First; Pregnancy-Associated Plasma Protein-A; Prospective Studies; Ultrasonography, Prenatal; Uterine Artery; Uterus

Videogame playing as distraction technique in course of venipuncture. - Minute, M; Badina, L; Cont, G; Montico, M; Ronfani, L; Barbi, E; Ventura, A (Pediatr Med Chir, 2012)
BACKGROUND: Needle-related procedures (venipuncture, intravenous cannulation) are the most common source of pain and distress for children. Reducing needle related pain and anxiety could be important in order to prevent further distress, especially for children needing multiple hospital admissions. The aim of the present open randomized controlled trial was to investigate the efficacy of adding an active distraction strategy (videogame) to EMLA premedication in needle-related pain in children. METHODS: One-hundred and nine children (4 -10 years of age) were prospectively recruited to enter in the study. Ninety-seven were randomized in two groups: CC group (conventional care: EMLA only) as control group and AD group (active distraction: EMLA plus videogame) as intervention group. Outcome measures were: self-reported pain by mean of FPS-R scale (main study outcome), observer-reported pain by FLACC scale, number of attempts for successful procedure. RESULTS: In both groups FPS-R median rate was 0 (interquartile range: 0-2), with significant pain (FPS-R > 4) reported by 9% of subjects. FLACC median rate was 1 in both groups (interquartile range 0-3 in CC group; 0-2 in AD group). The percentage of children with major pain (FLACC > 4) was 18% in CC group and 9% in AD group (p = 0.2). The median of necessary attempts to succeed in the procedures was 1 (interquartile range 1-2) in both groups.. CONCLUSION: Active distraction doesn't improve EMLA analgesia for iv cannulation and venipuncture. Even though, it resulted in an easily applicable strategy appreciated by children. This technique could be usefully investigated in other painful procedures.
Keywords: Anesthetics, Local; Child; Child, Preschool; Female; Humans; Lidocaine; Male; Pain; Phlebotomy; Prilocaine; Prospective Studies; Video Games

Interventions for the prevention of overweight and obesity in preschool children: a systematic review of randomized controlled trials. - Monasta, L; Batty, G D; Macaluso, A; Ronfani, L; Lutje, V; Bavcar, A; van Lenthe, F J; Brug, J; Cattaneo, A (Obes Rev, 2011)
The objective of this study was to analyse interventions for the prevention of overweight and obesity in children under 5 years of age. We carried out a systematic review focusing exclusively on randomized controlled trials (RCTs). Data sources include Medline, Cochrane Library, EMBASE, CINHAL, PsychInfo and Web of Science. Data were extracted from seventeen articles describing seven RCTs identified through electronic search, screening of references in systematic reviews, own files and contact with authors. RCTs were assessed with the Jadad scale. Four trials were carried out in preschool settings, one with an exclusive educational component, two with an exclusive physical activity component and one with both. Two trials were family-based, with education and counselling for parents and children. The remaining trial was carried out in maternity hospitals, with a training intervention on breastfeeding. None of the interventions had an effect in preventing overweight and obesity. The failure to show an effect may be due to the choice of outcomes, the quality of the RCTs, the suboptimal implementation of the interventions, the lack of focus on social and environmental determinants. More rigorous research is needed on interventions and on social and environmental factors that could impact on lifestyle.
Keywords: Child Nutrition Sciences; Child Nutritional Physiological Phenomena; Child, Preschool; Exercise; Female; Health Promotion; Humans; Life Style; Male; Obesity; Overweight; Randomized Controlled Trials as Topic

Periodontal infection and preterm birth: successful periodontal therapy reduces the risk of preterm birth. - Di Mario, S; Spettoli, D; Alessandrini, C; Erenbourg, A; Ronfani, L; Basevi, V (BJOG, 2011)
Keywords: Female; Humans; Periodontal Diseases; Pregnancy; Pregnancy Complications, Infectious; Premature Birth; Randomized Controlled Trials as Topic; Risk Factors

Gestational diabetes and fetal growth acceleration: induction of labour versus expectant management. - Alberico, S; Businelli, C; Wiesenfeld, U; Erenbourg, A; Maso, G; Piccoli, M; Ronfani, L (Minerva Ginecol, 2010)
AIM: The aim of the study was to compare elective induction of labour at 38 weeks versus expectant management in A1 and A2 gestational diabetes (GDM) pregnancies with fetal growth acceleration. Primary outcome of the study was C-section (CS) rate, while secondary outcomes were macrosomia incidence and adverse perinatal outcomes. METHODS: A retrospective cohort study was carried out. Data were collected between 1996 and 2006 and evaluated through patients' records analysis. Differences between the two study groups were investigated using non-parametric tests for continuous variables and χ2 test for categorical ones. RESULTS: There was no significant difference between induction and expectant management in terms of caesarean section rate. A trend favoring women in the induction group in terms of incidence of macrosomia and neonatal outcomes was identified, but results were not statistically significant. CONCLUSION: Labour induction at 38 weeks in GDM patients with fetal growth acceleration does not seem to determine an increased incidence of C-section in comparison to expectant management, particularly in case of maternal obesity.
Keywords: Adult; Body Mass Index; Cesarean Section; Diabetes, Gestational; Elective Surgical Procedures; Female; Fetal Development; Fetal Macrosomia; Gestational Age; Humans; Incidence; Infant, Newborn; Italy; Labor, Induced; Medical Records; Obesity; Pregnancy; Pregnancy Outcome; Retrospective Studies; Risk Factors; Statistics, Nonparametric; Watchful Waiting